2022
DOI: 10.1155/2022/6082700
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid Urothelial Carcinoma of the Bladder That Manifests Disseminated Carcinomatosis of the Bone Marrow: A Case Report of Extremely Rapid Progression

Abstract: Plasmacytoid urothelial carcinoma (PUC) of the bladder is a rare variant of invasive urothelial carcinoma (UC) with aggressive behavior. Despite its prognosis being poorer than that of conventional UC, a median overall survival of approximately 2 years is ensured when it is treated with radical cystectomy (RC), and few patients die within a few months of RC. In this paper, we report the case of a patient with PUC who developed widespread bone metastasis only 6 weeks after RC, which resulted in death within 2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…The diagnosis of disseminated carcinomatosis of the bone marrow from urothelial cancer in our patient underscores the diverse presentation of cancer, particularly the rare occurrence of cancer cells disseminating to the bone marrow from a primary urothelial carcinoma [ 16 ]. Soluble interleukin 2 receptor can increase highly in some cases in aggressive urothelial cancers [ 6 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The diagnosis of disseminated carcinomatosis of the bone marrow from urothelial cancer in our patient underscores the diverse presentation of cancer, particularly the rare occurrence of cancer cells disseminating to the bone marrow from a primary urothelial carcinoma [ 16 ]. Soluble interleukin 2 receptor can increase highly in some cases in aggressive urothelial cancers [ 6 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of disseminated carcinomatosis of the bone marrow from urothelial cancer in our patient underscores the diverse presentation of cancer, particularly the rare occurrence of cancer cells disseminating to the bone marrow from a primary urothelial carcinoma [ 16 ]. Soluble interleukin 2 receptor can increase highly in some cases in aggressive urothelial cancers [ 6 , 16 ]. Such cases highlight the need for high clinical suspicion and systematic investigation in patients presenting with unexplained systemic inflammation in primary care settings and general medicine [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, a study performed on 49 cases showed the positivity for cytokeratin, CD138, GATA3 and uroplakin II and negativity for e-cadherin. Loss of cell adhesion due to lack of E-cadherin is reported in many studies [17,18]. This is related with a higher disease grade and stage and can be explained by a loss of cadherin-1 (CDH1) mutation or hypermetilation of the promoter region [18,16].…”
Section: Discussionmentioning
confidence: 99%
“…Diffuse invasion of the bone marrow by tumor cells often results in disseminated intravascular coagulation (DIC) syndrome and microangiopathic hemolytic anemia. DCBM occurs in several tumors, including cancers of the stomach, 1 breast, 2 colon and rectum, 3 prostate, 4 tongue, 5 head and neck, 6 hepatocellular carcinoma, 7 intrahepatic cholangiocarcinoma, 8 duodenal, 9 pancreatic, 10 bladder, 11 uterine cervical, 12 and anal canal 13 carcinomas. In a follow‐up study of 2235 curatively resected gastric adenocarcinomas, there were four cases (0.2%) with matching DCBM 14 .…”
Section: Introductionmentioning
confidence: 99%